Antibody reactive to a novel autoantigen on the nondesmosomal keratinocyte surfaces leads to herpetiform pemphigus. (1st January 2019) - Yuan, H.; Pan, M.
Abstract: Linked Article:  Ishiura et al. Br J Dermatol 2019; 180 :187–92 .